Hybrid films of polyetherimide containing in situ grown Ag, Pd, and AgPd alloy nanoparticles: Synthesis route, morphology, and gas transport properties. Issue 18 (9th July 2014) - Simon, Sandra; Alcouffe, Pierre; Espuche, Eliane
ABSTRACT In this study, bimetallic/polymer films are synthesized from polyetherimide (PEI), palladium acetate and silver nitrate for a wide range of total metal amount (from 0 to 30 wt %) and different Ag to Pd molar ratios. Hybrid precursor films are first prepared from polymer/metal complex solutions and the metal nanoparticles are then generated within the PEI matrix by annealing the precursor film under specific conditions. Reference neat PEI films and monometallic films are prepared in the same conditions. Interestingly, formation of AgPd alloys directly within the polymer films is for the first time obtained from a very simple and environmentally friendly route. Based on X‐ray diffraction and transmission electron microscopy analyses, a nanostructuration mechanism is proposed. The interactions of hydrogen towards the nanocomposites are investigated and discussed as a function of the nanoparticle composition. The impact of the nanostructuration is also studied on H2, CO2, and He permeation properties. Significant improvement of barrier properties is achieved. The pertinent parameters of the gas transport are identified and modelled for each gas/composite system. Finally, from both morphological and gas transport analyses, it is concluded that in situ generation AgPd alloys with Pd to Ag ratio above 1 leads to very interesting and promising materials. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 1211–1220